Techno-Economic Feasibility Study for Organic and Plastic Waste Pyrolysis Pilot Plant in Malaysia - Lim M.; Tan E.S. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Organic and plastic waste (OPW) is diverted from landfills in order to lower carbon emissions. Nevertheless, modern pyrolysis techniques are frequently utilized in laboratories (using feedstocks that weigh less than 1 kg), which employ costly pure nitrogen gas (N2). This study developed a fast pyrolysis system to produce pyrolysis oil or liquid (PyOL) from OPW using flue gas as the pyrolysis agent. The added benefits included the efficient value-added chemical extractions and the non-thermal plasma reactor upgraded PyOL. OPW was also pyrolyzed at a pilot scale using flue gas fast pyrolysis in this study. In addition to lowering operational expenses associated with pure N2, flue gas reduced the lifecycle carbon emissions to create PyOL. The results indicated that considerable material agglomeration occurred during the OPW pyrolysis with an organic-to-plastic-waste (O/P) ratio of 30/70. Furthermore, the liquid yields were 5.2% and 5.5% when O/P was 100/0 (305 C) and 99.5/0.5 (354 C), respectively. The liquid yields also increased when polymers (polypropylene) were added, enhancing the aromatics. Two cases were employed to study their techno-economic feasibility: PyOL-based production and chemical-extraction plants. The mitigated CO2 from the redirected OPW and flue gas produced the highest revenue in terms of carbon credits. Moreover, the carbon price (from RM 100 to 150 per ton of CO2) was the most important factor impacting the economic viability in both cases. Plant capacities higher than 10,000 kg/h were economically viable for the PyOL-based plants, whereas capacities greater than 1000 kg/h were financially feasible for chemical-extraction plants. Overall, the study found that the pyrolysis of OPW in flue gas is a viable waste-to-energy technology. The low liquid yield is offset by the carbon credits that can be earned, making the process economically feasible. 2023 by the authors.